From Knowledge to Action: Exploring Green Intellectual Capital’s Role in Sustainable Organizational Performance for Millennials - Nawangsari, Lenny Christina; Siswanti, Indra; Arijanto, Agus; Wahyu, Mas (International Review of Management and Marketing, 2024)
In today’s competitive landscape, the role of Green Intellectual Capital in driving Sustainable Organizational Performance is receiving increasing attention. Organizations are under pressure to adopt sustainable practices, so exploring the influence of intellectual capital on performance is important. This study aims to examine the effect of Green Intellectual Capital consisting of Green Human Capital, Green Relational Capital and Green Structural Capital on Sustainable Organizational Performance, with Green Innovation Behavior as a mediating variable and Perceived Green Organizational Support as a moderating factor. The research design used was quantitative involving 200 millennial managers and the data was analysed using Partial Least Squares (PLS). The results show that to achieve sustainable organizational performance, millennial managers need to focus their efforts on improving Green Structural Capital and encouraging Green Innovation Behavior. In addition, the development of Gren Human Capital and Green Relational Capital should be geared towards increasing Green Innovation as a pathway to achieving sustainability goals. Perceived Green Organizational Support is not enough to strengthen the relationship of innovation and performance, so a more holistic approach in promoting sustainability across the organization is needed. The novelty of this research lies in its focus on millennial managers and the complex interconnectedness of different components of Green Intellectual Capital. The findings suggest that organizations should prioritize increasing Green Structural Capital and encouraging Green Innovation Behaviors. Future research should explore other moderating factors, such as leadership style, to deepen understanding of the conditions that amplify the impact of green innovation on sustainable performance.